Change in microstructural characteristics of laser powder bed fused Al–Fe binary alloy at elevated temperature. (20th January 2022) - Qi, Xing; Takata, Naoki; Suzuki, Asuka; Kobashi, Makoto; Kato, Masaki
Highlights: Al–Fe alloys built via laser powder bed fusion show high microstructural stability. As-built samples showed multi-semi-cylindrical patterns corresponding to melt pools. Metastable nanoscale Al6 Fe phases were uniformly dispersed inside melt pools. Stable θ-Al13 Fe4 phases were locally formed and coarsened upon exposure to 300 °C. Dispersed fine particles showed a pinning effect on grain-boundary migration. Abstract: The present study addressed the change in the microstructure of Al–2.5 wt% Fe binary alloy produced using laser powder bed fusion (L-PBF) technique by thermal exposure at 300 °C, and the associated mechanical and thermal properties were systematically examined as well. Multi-semi-cylindrical patterns corresponding to melt pools in the microstructure were macroscopically observed for the as-manufactured sample. No change in the melt-pool morphology was observed after thermal exposure for 1000 h. Inside the melt pools, a large number of the nanoscale metastable Al6 Fe phase particles were uniformly distributed inside columnar grains of the α-Al matrix containing concentrated solute Fe in supersaturation. The sequential formation and coarsening of stable θ-Al13 Fe4 phases were observed upon exposure to a 300 °C environment, but a considerable amount of nano-sized metastable Al6 Fe phases remained even after 1000 h. Furthermore, the thermal exposure continuously reduced the concentration of solute Fe atoms in the α-Al matrix. No significant grain growth was found in α-Al matrix after 1000 h owing to the pinning effect of the dispersed fine particles on grain boundary migration. These results demonstrate a sluggish change in microstructural morphologies of the Al–2.5 wt% Fe alloy. The quantified microstructural parameters addressed dominant strengthening contributions by the solid solution of Fe element and Orowan strengthening mechanism by fine Al–Fe intermetallics in the L-PBF-produced alloy. The high strength level was sustained even after being exposed to 300 °C for long periods. The superior balance of mechanical properties and thermal conductivity can be achieved in the experimental alloys by taking advantage of the various microstructural parameters related to the Al–Fe intermetallic phases and α-Al matrix. Graphical Abstract: Image, graphical abstract